2017
DOI: 10.1097/rlu.0000000000001506
|View full text |Cite
|
Sign up to set email alerts
|

PET MRI Coregistration in Intractable Epilepsy and Gray Matter Heterotopia

Abstract: A 25-year-old woman with intractable seizures underwent FDG PET/MRI for seizure focus localization. MRI demonstrated bilateral carpetlike nodular subependymal gray matter and asymmetrical focal dilatation in the right temporal horn. PET/MRI showed increased FDG within subependymal gray matter with significant hypometabolism in right anterior temporal lobe. EEG and ictal semiology confirmed the right temporal seizure origin. This case highlights the importance of identification of gray matter heterotopia on FDG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…In line with our results, Popescu et al, Mirandola et al, and Bund et al observed a broad spectrum of FDG uptake patterns in heterotopic nodules in patients with PNH 24,27,32 . Contrarily, many other reports documented that the 18 F‐FDG uptake of GMH is often similar to that of the regular cortex 14,33–37 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with our results, Popescu et al, Mirandola et al, and Bund et al observed a broad spectrum of FDG uptake patterns in heterotopic nodules in patients with PNH 24,27,32 . Contrarily, many other reports documented that the 18 F‐FDG uptake of GMH is often similar to that of the regular cortex 14,33–37 …”
Section: Discussionsupporting
confidence: 92%
“…[28][29][30][31] We found that many patients had hypometabolic GMHs on 18 Contrarily, many other reports documented that the 18 F-FDG uptake of GMH is often similar to that of the regular cortex. 14,[33][34][35][36][37] Few of the aforementioned studies and case series investigated the clinical relevance of the metabolism of the heterotopic nodules. For instance, Popescu et al 24 found an inverse correlation between the presence of hypometabolic nodules and postsurgical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, only a few reports featuring small patient samples or single cases can be found in literature, reporting on functional imaging of subcortical heterotopia by means of 18 F‐FDG PET/CT and 99m Tc‐HMPAO SPECT. These studies reported that the metabolism and perfusion of subcortical heterotopia are similar or somewhat increased compared to the overlying cortex, thus indicating a certain degree of metabolism and, by extension, of functional activity . It still remains unclear whether these neurons act as epileptic foci or they behave similarly to normally located neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In drug-resistant PNH-related seizures, FDG PET seems to help SEEG procedure, offering a better sampling of electrodes implantation in not only intralesional topography (ictal onset zone and early propagation epileptogenic zone) but also at distance (late propagation epileptogenic zone). Fused with MRI, it seems to predict the topography of the epileptogenic zone network 1 . This noninvasive technique helps to understand the role of PNH in the epileptogenic zone network, 2 defined by intracerebral monitoring.…”
mentioning
confidence: 99%